2006
DOI: 10.1021/jp061517l
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Pattern of Small Silicon Oxide Clusters:  Structures and Stability of Si6On (n = 1−12)

Abstract: We have performed systematic ab initio calculations to study the structures and stability of Si(6)O(n)() clusters (n = 1-12) in order to understand the oxidation process in silicon systems. Our calculation results show that oxidation pattern of the small silicon cluster, with continuous addition of O atoms, extends from one side to the entire Si cluster. Si atoms are found to be separated from the pure Si cluster one-by-one by insertion of oxygen into the Si-O bonds. From fragmentation energy analyses, it is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 22 publications
9
35
0
Order By: Relevance
“…Figure 8 shows that the best Si 6 O 6 isomer is the less stable among these silicon-oxide systems, as we can see from the BE I curve. This observation was also reported by Zang et al 39 We study some fragmentation pathways and the corresponding energies for the most stable structures of the series Si 6 Figure 9 shows a similar behavior for the LUMO-HOMO gap and the fragmentation energy against the number of oxygen atoms for the most stable isomer of the series Si 6 O m ͑m =1-11͒, except Si 6 O 5 . Clusters with high minimum fragmentation energy are particularly stable while large LUMO-HOMO gaps are indicative of chemical inertness.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Figure 8 shows that the best Si 6 O 6 isomer is the less stable among these silicon-oxide systems, as we can see from the BE I curve. This observation was also reported by Zang et al 39 We study some fragmentation pathways and the corresponding energies for the most stable structures of the series Si 6 Figure 9 shows a similar behavior for the LUMO-HOMO gap and the fragmentation energy against the number of oxygen atoms for the most stable isomer of the series Si 6 O m ͑m =1-11͒, except Si 6 O 5 . Clusters with high minimum fragmentation energy are particularly stable while large LUMO-HOMO gaps are indicative of chemical inertness.…”
Section: Resultssupporting
confidence: 86%
“…This global search assures that Si 6 O m isomers are produced from a full exploration of the MSINDO/DFT potential energy, without the limitations of DFT relaxed structures obtained by adding m oxygen atoms, one by one, to different Si 6 isomers. In an attempt to understand better the electronic properties in the formation of these clusters, 39,40 we studied two series: ͑i͒ Si 6 O m ͑m =2,3,4,5,6͒, which can be thought as small Si n clusters plus small oxide fragments and ͑ii͒ Si 6 O m ͑m =9,10,11͒, clusters rich in oxygen, which show that the more stable ones are those for which the silicon atoms are more coordinated to oxygen ones.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and co-workers reported that the binding energies per O atom for Si 6 O n (n=1-12) increased with the numbers of O atoms at first, and then decreased when n>8 [19]. The similar tendency also was found in Si 7 O n (n=1-14) clusters [20].…”
Section: Si 10-m O M (M=1-8) Clustersmentioning
confidence: 52%
“…In recent years, the oxide silicon was investigated in both experiment [1,4,5,[10][11][12][13] and theory [10][11][12][13][14][15][16][17][18][19][20][21] for its broad prospect in the application. Desjardin and co-workers [1] studied oxidation of Si (111)-(7×7) surface by STM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation